FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME DAN PORSI PEMBIAYAAN BERBASIS BAGI HASIL PADA PERBANKAN SYARIAH DI INDONESIA - Nisa Furqaini; Rizal Yaya (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
This study aimed to determine the effect of third-party funds (Dana Pihak Ketiga/DPK), the level of profit sharing, non-performing financing (NPF), and the capital adequacy ratio (CAR) to the financing volume and financing portion based on profit sharing on Islamic banking in Indonesia. The samples used were 10 Islamic Banks for period September 2011 to December 2014. Using multiple linear regression analysis, results obtained third party funds, the level of profit sharing; non-performing financing and capital adequacy ratio significantly influence the financing volume and financing portion on profit sharing. The partial test result show that capital adequacy ratio have positive and significant impact to the financing volume and financing portion. On the other hand third party funds only positively influence on the financing volume; non-performing financing negatively affect the financing volume and the financing portion on profit sharing; the level of profit sharing did not affect the financing volume and financing portion on profit sharing.